Spectrum without Bounds, Networks without Borders - DA SILVA, LUIZ; DOYLE, LINDA; FORDE, TIM (IEEE, 2014)
The purpose of this paper is to present a vision for future mobile and wireless networks. The vision, which we call Networks without Borders (NwoB), is based on a market-place of virtual network operators which construct networks from a pool of shared resources (e.g. basestations, spectrum, core network components, cloud resources, processing capabilities etc.). The resources will be sourced from traditional industry players as well as crowdsourced from individuals. The paper describes this approach from a value-chain perspective. The proposed value-chain is substantially different from the value-chain models that are currently used to illustrate mobile and wireless networks. The economic imperatives and innovation drivers for this approach are discussed. Early work showing the promise of this vision is presented. This work focuses on diverse examples which advocate the removal of traditional and historical restrictions on spectrum and infrastructure and move towards more dynamic use of shared resources. In the first example we look at how frequency-division-duplexing (FDD) and time-division- duplexing (TDD) restrictions on spectrum usage can be relaxed; we remove the borders between TDD and FDD. In the second example we look at the aggregation and pooling of corporate infrastructure which uses exclusive spectrum and removes the borders between different mobile operators. Finally we look at the aggregation of user-deployed or crowdsourced infrastructure that opportunistically uses spectrum and removes the borders between independently deployed hotspots. These are starting points and the full realization of the vision will involve more dynamic access to spectrum and more extensive sharing of infrastructure. Hence, the final part of the paper describes the resulting research challenges
Proceedings of the IEEE
PUBLISHED
Keywords: Wireless Networks